CMET-11. LEPTOMENINGEAL MELANOMA METASTASIS PRESENTING AS INTRAVENTRICULAR AND SUBARACHNOID HEMORRHAGE. (5th November 2018) - Graham, Maya; Jagannathan, Radhika; Rubens, Elayna; Wolchok, Jedd; Wu, Synphen
Abstract: Leptomeningeal spread of cancer can have protean presentations, increasing the difficulty of making this diagnosis. We present the case of a 77-year-old man with prior metastatic melanoma who presented with spontaneous headache that worsened over several days, and was found to have both intraventricular and cortical subarachnoid hemorrhage on CT head. His neurological exam was unremarkable. MRI of the brain with contrast confirmed the CT findings and did not reveal any evidence of parenchymal or leptomeningeal metastases. MR angiogram followed by a conventional angiogram did not demonstrate any vascular abnormalities. Cerebrospinal fluid examination revealed 110 white blood cells, 34000 red blood cells, and protein of 160. Cytology returned positive for malignant melanoma cells. No additional sites of disease were found on further evaluation with MRI spine and CT of the chest, abdomen and pelvis. In retrospect, the patient had endorsed some fluctuating nausea and fatigue three months prior to presentation, as well as positional vertigo two weeks prior to presentation. His oncologic history was notable for prior immunotherapy with ipilimumab, as well as diagnosis of dural-based brain metastases two years earlier, for which he underwent surgical resection and radiation therapy. He had no evidence of disease for one year prior to this new diagnosis of leptomeningeal involvement. This case highlights an unusual presentation of leptomeningeal metastasis and underscores the importance of maintaining heightened suspicion for this diagnosis when evaluating subarachnoid hemorrhage in a cancer patient, especially in the case of melanoma. It raises the question of whether this particular cancer type or the patient's prior immunotherapy contributed to his presentation, and emphasizes the need for further elucidation of the biology of leptomeningeal metastasis.